Numerical Solutions of the Second Order Initial Value Problems by Haar Wavelet Method - Bushra A.Taha – Mahmood A.Arif ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2019)
In this paper, we apply Haar wavelet method for solving seconed order initial value problems of ordinary differential equation. The fundamental idea of Haar wavelet method is to convert the differential equations into a group of algebraic equations, which involves a finite number or variables. We compared this numerical results with the exact solution and other known methods.